Soil acidity limits wheat yield in dryland regions of the Inland Pacific Northwest. Issue 2 (23rd March 2017) - Ghimire, Rajan; Machado, Stephen
Abstract : In an ongoing long‐term experiment, the influence of tillage and N fertilizer management on soil acidity, soil organic matter, and wheat yield in dryland winter wheat–summer fallow systems was examined. Earn 0.5 CEUs in Soil & Water Management by reading this article and taking the quiz at www.certifiedcropadviser.org/certifications/self‐study/829 .